Evaluation of the application for new alternative biodiesel production process for rendered fat including Category 1 animal by‐products (BDI‐RepCat® process, AT). (15th April 2021) - ; Koutsoumanis, Konstantinos; Allende, Ana; Bolton, Declan; Bover‐Cid, Sara; Chemaly, Marianne; Davies, Robert; De Cesare, Alessandra; Herman, Lieve; Hilbert, Friederike; Lindqvist, Roland; Nauta, Maarten; et al.
Abstract: A new alternative method for the production of biodiesel from rendered fat, including animal by‐product (ABP) Category 1 tallow, was evaluated. The method consists of a conversion phase, based on esterification and transesterification in a single step (at temperature ≥ 200°C, pressure ≥ 70 bar with a retention time ≥ 15 min), using MgO as a catalyst and in the presence of methanol (10–15%), followed by vacuum distillation (at ≥ 150°C, ≤ 10 mbar) of the end‐product, biodiesel and the co‐product, glycerine. Prions (PrP S c ), which are abnormal isoforms of the prion protein, were considered by the applicant to be the most resistant hazard. In accordance with previous EFSA Opinions and current expert evaluation, a reduction in prion infectivity, or detectable PrP S c, of at least 6 log10 should be achieved for the process to be considered equivalent to the processing method laid down in the Regulation (EU) No 142/2011. Published data from an experimental replication of the conversion step of the biodiesel production process under consideration were provided, which showed an at least 6 log10 reduction in detectable PrP S c, by Western blot, in tallow that had been spiked with murine and human prion strains. In addition, it was demonstrated that the presence of methanol does not affect the recovery or detection of PrP S c from a biodiesel substrate. Based on scientific literature, the vacuum distillation step has been shown to be capable of achieving an additional 3 log10 reduction in PrP S c . Therefore, the proposed alternative method is considered to be at least equivalent to the processing method laid down in the legislation for the production of biodiesel from raw materials including Category 1 ABP.